2018
DOI: 10.1039/c8dt03595d
|View full text |Cite
|
Sign up to set email alerts
|

Electronic density distribution of Mn–N bonds by a tuning effect through partial replacement of Mn by Co or Ni in a sodium-rich hexacyanoferrate and its influence on the stability as a cathode for Na-ion batteries

Abstract: This study evaluates the effect of equimolar substitution of manganese by cobalt or nickel in hexacyanoferrate open frameworks as electrode for Na-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 56 publications
0
22
0
4
Order By: Relevance
“…The N‐coordinated TMs can be partially substituted by a single element or multiple elements in order to adjust the lattice parameters and redox property. Owing to the “zero‐strain” character and higher conductivity of NiHCFs, [ 25,178 ] Ni‐substitution has been widely employed to optimize the performances of NaFeHCFs, [ 179–181 ] KFeHCFs, [ 182,183 ] NaMnHCFs, [ 121,184,185 ] NaCoHCFs, [ 124,186 ] and NaCuHCFs. [ 19,187 ] In addition, the redox‐active Co and Fe have also been used to modify NaMnHCFs [ 102,185,188 ] and KMnHCFs.…”
Section: Elemental Substitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N‐coordinated TMs can be partially substituted by a single element or multiple elements in order to adjust the lattice parameters and redox property. Owing to the “zero‐strain” character and higher conductivity of NiHCFs, [ 25,178 ] Ni‐substitution has been widely employed to optimize the performances of NaFeHCFs, [ 179–181 ] KFeHCFs, [ 182,183 ] NaMnHCFs, [ 121,184,185 ] NaCoHCFs, [ 124,186 ] and NaCuHCFs. [ 19,187 ] In addition, the redox‐active Co and Fe have also been used to modify NaMnHCFs [ 102,185,188 ] and KMnHCFs.…”
Section: Elemental Substitutionmentioning
confidence: 99%
“…It is observed that the Fe‐substitution is most desired in terms of capacity and stability, while the Ni‐substitution can best promote the electrode kinetics. Similarly, Oliver‐Tolentino et al reported a superior effect of Ni‐substitution on NaMnHCF by comparing the structures and electrochemical behaviors of Na M x Mn 1‒ x HCF ( x = 0.55) with M = Ni, Co. [ 185 ] Detailed analyses indicate that both Co‐ and Ni‐substitution can improve the covalent character of MnN bonds, which will increase the separation between the bonding and antibonding orbitals. The charge density around Fe is also modulated by the polarizing power of Co and Ni, which induces decreased energy of Fe t 2g orbitals.…”
Section: Elemental Substitutionmentioning
confidence: 99%
“…PBAs can be utilized as cathode and anode materials for alkaline ion storage (Li + /Na + /K + ), due to their open frameworks, which offer large spaces for alkaline ion insertion and extraction . The mechanism for the use of PBAs for alkaline ion storage can be expressed by Equation :normalAxT[]normalMCN6xnormalA++T[]normalMCN6x…”
Section: Applicationsmentioning
confidence: 99%
“…Owing to its open framework, the alkaline ions can be extracted/intercalated reversibly from/into the PBAs, making them suitable as cathode materials for alkaline ion batteries (Li + , Na + , K + , etc.) and as electrodes for supercapacitors with organic or aqueous electrolytes . Some defects and crystal water inevitably remain in PBAs due to their preparation in aqueous solution, meaning that they can be used as the host for hydrogen storage .…”
Section: Introductionmentioning
confidence: 99%
“…Infrared spectra are sensitive to the coordinate environment of the chemical bond. In the PBA synthesis process, when the Fe­(CN) 6 3–/4– group coordinates with the transition metal, the charge density at the N end shifts towards the transition metal, the CN binding energy shifts to higher values, , and the CN group vibration band should shift to higher wavenumbers in infrared spectroscopy. According to the sensitivity of CN to its bonding environment, in situ Fourier transform infrared (FTIR) spectroscopy characterization is an effective way to monitor the formation process of PBA frameworks.…”
Section: Introductionmentioning
confidence: 99%